2020
DOI: 10.33233/rbfex.v19i5.4393
|View full text |Cite
|
Sign up to set email alerts
|

Responses of myokines concentrations from exercise stimulus: a systematic review

Abstract: The skeletal muscle is the largest endocrine organ of human body and have this role through peptides and proteins known as myokines. The myokines are cytokines that are produced and secreted by the skeletal muscle in response to the stimulus of contraction, acting locally and/or be released in the circulation and influence other distant tissues. Physical exercise is a potent stimulus for molecular adaptations in the organism, and when practiced with regularity, promotes structural and functional adaptations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the mechanisms that lead to physical exercise to reduce the disease symptoms are still not well understood. However, it is known that physical activity modulates the secretion of a series of fundamental cytokines for body homeostasis [23]. Iftikhar et al [24] demonstrated that the effects of physical exercise on sleep apnea are independent of a reduction in BMI and body weight.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms that lead to physical exercise to reduce the disease symptoms are still not well understood. However, it is known that physical activity modulates the secretion of a series of fundamental cytokines for body homeostasis [23]. Iftikhar et al [24] demonstrated that the effects of physical exercise on sleep apnea are independent of a reduction in BMI and body weight.…”
Section: Discussionmentioning
confidence: 99%